Lipophilicity vs. antitumor activity of carboxylatoplatinum(IV) complexes - Song, R; Kim, KM; Sohn, YS (KOREAN CHEMICAL SOC, 2000)
Acylation of an intermediate tetrahydroxoplatinum(IV) complex, [Pt(OH))(4)(dach)] (dach = trans-(+/-)-1,2-diaminocyclohexanl), with one or two kinds of carboxylic anhydrides in stepwise manner afforded various carboxylatoplatinum(IV) complexes, [Pt(O2CR)(x)(OR')(4-x)(dach)] (R = (CH2)(3)CH3 or C(CH3)(3), R' = H or OCCH3, and x = 1-4) with a wide range of lipophilicity. The title complexes were subjected to bioassay using the murine leukemia L1210 cell line, and in particular, their in vivo oral antitumor activity was attempted to correlate with their lipophilicity and water solubility. The most orally active complex exhibited intermediate lipophilicity and water solubility, but it has been found that an exact relationship between the lipophilicity and oral anticancer activity could not be established, since the lipophilicity of the complexes is not the sole parameter to determine the oral activity. One of the important intermediate complexes partially substituted was subjected to X-ray analysis for positional assignment of the substituted group:[Pt(OPiv)(3)(OH)(dach)] crystallizes in the tetragonal system, space group P (4) over bar2(1C) with a = 21.161(3)Angstrom b = 21.161(6) Angstrom, c = 12.816(3) Angstrom, alpha= beta = gamma= 90 degrees, V = 5739(2) Angstrom and Z = 8.
Keywords: CARCINOMA CELL-LINES; PLATINUM COMPLEX; CARBOXYLATION; CYTOTOXICITY; RESISTANT; ISOMERS; CRYSTAL; WATER